Fabrication and characterization of polymeric and nanostructured carbon nitride thin films : a simple difference in electrode distance / Richard anak Ritikos - Ritikos, Richard (2011)
This work gives an insight on the fabrication and characterization of two distinctly different hydrogenated carbon nitride CNx:H structured films showing either polymeric, p-CNx:H or nanostructured, ns-CNx:H film growth. These structures were obtained using radio frequency (rf) plasma enhanced chemical vapour deposition employing a parallel-plate electrode configuration, under the same deposition parameters except for the change in the electrode distance. It was this simple change in the distance which induced the structural transformation from p-CNx:H films obtained at distance of six to three cm, to the ns-CNx:H films produced at two to one cm. Each type of film showed its own unique characteristics. For the p-CNx:H films deposited at an electrode distance of 5 cm, their PL spectra showed two main peaks assumed to be attributed to the presence of sp2 clusters and nitrogen bonding in the films. Further studies showed that the optimized rf power and nitrogen-to-methane N2:CH4 gas-flowrate ratio to obtain p-CNx:H films with the highest PL intensities were 80 W and 0.70, respectively. There appeared to be no direct correlation between the PL properties and optical energy gap. However, the PL characteristics were dependent on the N content in the films. From extensive bonding studies carried out on these films, it was found that N is incorporated most significantly through nitrile, isonitrile and sp2-CN bonding configurations. Also, these films were thermally stable when annealed in nitrogen up to temperatures of 500 °C, though the PL intensities start to decline even from 200 °C. The recombination centers which produced these high PL intensities were attributed to the CHn, CN and the isolated and/or fused aromatic rings bonded to nitrile (−C≡N) which may contribute significantly as recombination centers. While the studies of p-CNx:H films were focused on their PL characteristics, a more fundamental approach was taken in the study of ns-CNx:H. These novel ns-CNx:H films were obtained at low deposition temperatures without the use of metal-catalyst or template, and could be grown directly on the bare silicon and quartz substrates. The focus of the study of these ns-CNx:H films was on the formation of vertically aligned CNx:H nanorods and their growth mechanism. The optimized parameters for the formation these nanorods were determined to be at Prf of 80 W and N2:CH4 ratio of 0.70. This coincided with the maximum N content and preferential bonding of isonitrile bonded to fused or isolated aromatic rings in the films. These nanorods were made up of C nanographitic sp2 clusters embedded in a carbon-nitrogen amorphous matrix which surrounded, encapsulated and held them together. The growth mechanism of these vertically aligned nanorods was proposed. In the optimization studies of both materials, one fascinating conclusion was uncovered. The optimized deposition parameters for both exceptional characteristics of these structured films were the same. It is the simply the difference in electrode distance at these optimal Prf and N2:CH4 ratio, which induces the formation of these two significantly different structured films.